Planeamiento estratégico y cumplimiento de metas en la Municipalidad Provincial de Maynas año 2019 - Carrasco Calderón, María Angélica (2021)
The present investigation in the Maynas’ Provincial Municipality begins with certain deficiencies in the application of strategic planning in public management, for which the collaborators consider that due to these factors the institution is not meeting the goals. Given this, it has been proposed as a general objective to determine the relationship between strategic planning and the fulfillment of goals in the Maynas’ Provincial Municipality, 2019; opting for a descriptive and correlational research, of non-experimental design, for which a sample of 184 people has been taken from a population of 366 workers, therefore, it has been seen as pertinent to apply the survey technique and the questionnaire as a data collection instrument; The results were obtained that strategic planning and the fulfillment of goals in the MPM are significantly related, an instance that is corroborated by Spearman's Rho statistic, with a correlation coefficient of 0.742 and a degree of significance of 0.000. It was concluded that it was determined that strategic planning has been developed on a regular basis, since to a large extent this is due to the minimal interest in carrying out a prior analysis of the needs of the institution; Likewise, it has been possible to determine that the goals are being met on a regular basis, a situation that is due to the lack of knowledge of the budgetary programming of the projects, knowledge about norms and procedures for the programming and registration of projects.